Prediction of pregnancy disorders in female workers in the industrial sector - Martiana, Tri; Rahman, Firman Suryadi; Martini, Santi; Paskarini, Indriati; Melaniani, Soenarnatalina; Kusumawardani, Ajeng; Jalaludin, Juliana; Abd Mumin, Khadizah H. (Elsevier, 2024)
Context: As female workers face a higher risk of exposure to workplace hazards than women in general, it is imperative that measures be put in place in the workplace to ensure safe and healthy pregnancies. Objectives: This study aimed to analyze the effects of occupational hazards in the workplace environment on the potential for pregnancy disorders experienced by female workers. Methods: This was an analytical, observational study with a case-control design. The participants were female workers who worked in industrial environments in both formal and nonformal in- dustries. The inclusion criteria used in this study were female workers who had been or were pregnant at the time of the study, had worked in the industrial sector for at least one year, and did not smoke or consume alcohol. The samples were collected from 144 female workers. Midwives assisted in collecting data and conducting examinations of female workers. This study was con- ducted in Surabaya and Sidoarjo between June and December 2020. Data were analyzed descriptively, and a multivariable logistic regression test was performed. The study was con- ducted in accordance with the health protocols and prevention of COVID-19. Results: The results showed that occupational hazards in the workplace environment that affect pregnancy disorders include workload (p = 0.004, OR = 28.676 (2.979–276.076); hot working environment (p = 0.014, OR = 3.077 (1.254–7.552); strong odors (p = 0.017, OR = 7.640 (1.436–40.656); shift work (p = 0.023, OR = 8.063 (1.337–48.623); irregular shift work (p = 0.018, OR = 7.371 (1.409–38.557); and night shift work (p = 0.015, OR = 11.780 (1.605–86.450). Conclusions: Companies are expected to pay special attention to female workers regarding various workplace controls to prevent potential pregnancy-related disorders.